Análise de acidentes fatais investigados pelo MTE de acordo com o porte da empresa: Estado de Sâo Paulo - Forte, Viviane de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O estudo avalia os acidentes de trabalho fatais analisados pelo Ministério do Trabalho e Emprego no Estado de São Paulo, entre os anos de 2001 a 2006. Distribuir os acidentes analisados segundo o fator imediato de mortalidade e os fatores causais por atividade econômica e porte da organização, além de classificar os acidentes segundo as fases de controle de risco das empresas definidos por Michel Monteau. A principal fonte de informações utilizada nesta dissertação é o banco de análise de acidentes do trabalho do Ministério do Trabalho e Emprego, que está inserido no Sistema Federal de Inspeção do Trabalho – SFIT, que registra todas as fiscalizações realizadas por este órgão. Foram analisados 534 óbitos ocupacionais registrados no banco de análises, que forneceu diversas informações acerca dos acidentes, como o fator imediato de mortalidade, as causas selecionadas pelos analistas, descrição dos eventos, dentre outras. Nas atividades econômicas avaliadas, quais sejam, agricultura, indústria, construção, comércio e serviços, os seguintes fatores de mortalidade estiveram associados em maior número de casos aos acidentes: impacto causado por objeto lançado, projetado ou em queda; queda durante realização de serviços em telhado; exposição a outras linhas de distribuição e consumo de corrente elétrica e apertado, colhido, comprimido ou esmagado dentro de ou entre objetos. As causas relacionadas aos acidentes são organizadas por grupo, sendo que os fatores da tarefa foram os mais selecionados, seguidos pelo grupo demais grupos de fatores da organização e gerenciamento ou fatores da organização e gerenciamento das atividades / da produção. Problemas relacionados aos fatores do ambiente corresponderam ao quarto grupo mais relatado em todas as atividades como causas geradoras dos óbitos...

The study evaluates the fatal industrial accidents analyzed by the Ministry of Labor and Employment in São Paulo´s state, between 2001 to 2006 years. Distribute the accidents analyzed by the factor of immediate mortality and the causal factors for economic activity and size of company, in addition to classify the accident according to the phases of controlling risk of businesses defined by Michel Monteau. The main source of information used in this dissertation is the seat of analysis of accidents in the work of the Ministry of Labor and Employment, which is in the Federal System of Labor Inspection - IFCT, which records all the investigations carried out by the latter. We analyzed 534 occupational deaths recorded in the bank for analysis, which provided many details about the accident, as the immediate factor of mortality, the causes selected by analysts, description of events, among others. In the economic activities evaluated, namely, agriculture, industry, construction, trade and services, the following factors of mortality were associated in many cases the accidents: impact of object launched, projected or falling; fall during execution of services in roof; exposure to other lines of distribution and consumption of electric current and tight, harvested, crushed or compressed within or between objects. The causes related to accidents are organized by group, and the factors of the task were the most selected, followed by the other groups of the organization and management factors or factors of the organization and management of activities / production. Problems related to environmental factors were the fourth group most often reported in all activities as generating causes of the deaths. The types of Monteau to classify the stages of controlling risk of establishments showed that, among the cases examined, small businesses tend to have more... (Complete abstract click electronic access below)
Keywords: Acidentes do trabalho; Ministério do Trabalho; Work accident; Death; Fatal accident